2021
DOI: 10.1177/0954407020983077
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of static pressure circumferential double-peak distribution in a centrifugal compressor under the action of downstream boundary

Abstract: In the centrifugal compressor applied in the automobile turbochargers, the asymmetric structure of volute causes the non-uniform flow field in the impeller and compressor stall. The non-uniformity of the flow field in the compressor can be reflected by the casing-wall static pressure distribution. In this study, by removing the volute and directly imposing different simplified static pressure boundary conditions at the diffuser outlet, the formation mechanism of casing-wall static pressure circumferential doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The stall cell is first produced at the impeller inlet circumferential region, corresponding to the first high static pressure strip induced by the VT. With a further decrease in the flow rate, the LE spillage also appears at the impeller inlet circumferential position corresponding to another high static pressure strip. PD-DP was also displayed in the studies of Tamaki et al, 24 Harley et al, 25 and Zheng et al 26 Moreover, Su et al 29,30 further elaborated that the PD-DP is caused by the redistribution of the impeller outlet flow rate, and the static pressure strips are gradually created from the downstream to the upstream of the compressor.…”
Section: Introductionmentioning
confidence: 85%
“…The stall cell is first produced at the impeller inlet circumferential region, corresponding to the first high static pressure strip induced by the VT. With a further decrease in the flow rate, the LE spillage also appears at the impeller inlet circumferential position corresponding to another high static pressure strip. PD-DP was also displayed in the studies of Tamaki et al, 24 Harley et al, 25 and Zheng et al 26 Moreover, Su et al 29,30 further elaborated that the PD-DP is caused by the redistribution of the impeller outlet flow rate, and the static pressure strips are gradually created from the downstream to the upstream of the compressor.…”
Section: Introductionmentioning
confidence: 85%
“…Zheng et al investigated the volute-induced non-axisymmetrical flow in a centrifugal compressor, 10,11 and developed non-axisymmetrical self-recirculation casing treatment 12 and a volute design method. 13 The study of Yang et al 14 and Su et al 15 showed that the volute could determine both the static pressure distribution on the casing wall and the circumferential position of stall inception. Moreover, Fu et al 16 investigated the same centrifugal compressor with vaned/vaneless diffuser and found that the vaned diffuser reduces the potential effect of volute but could not eliminate the “locking effect” of stall inception.…”
Section: Introductionmentioning
confidence: 99%